2010
DOI: 10.1016/j.jvs.2009.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Walking economy before and after the onset of claudication pain in patients with peripheral arterial disease

Abstract: Purposes To determine the walking economy before and after the onset of claudication pain in patients with peripheral arterial disease (PAD), and to identify predictors of the change in walking economy following the onset of claudication pain. Methods A total of thirty-nine patients with PAD were studied, in which 29 experienced claudication (Pain group) during a constant load walking economy treadmill test (speed = 2.0 mph, grade = 0%) and 10 were pain-free during this test (Pain-Free group). Patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 37 publications
4
33
0
7
Order By: Relevance
“…These findings underscore the complexity of the genesis of functional impairment in individuals with IC (2). It is well established that walking impairment in these patients stem from a combination of several mechanisms that range from intrinsic skeletal muscle abnormalities to poor walking economy (2,16,40). In essence, targeting only one of the multiple mechanisms that underlie the exercise intolerance in these individuals might be insufficient to promote an acute improvement in performance (8).…”
Section: Effects Of Sildenafil On Muscle Oxygenationmentioning
confidence: 99%
“…These findings underscore the complexity of the genesis of functional impairment in individuals with IC (2). It is well established that walking impairment in these patients stem from a combination of several mechanisms that range from intrinsic skeletal muscle abnormalities to poor walking economy (2,16,40). In essence, targeting only one of the multiple mechanisms that underlie the exercise intolerance in these individuals might be insufficient to promote an acute improvement in performance (8).…”
Section: Effects Of Sildenafil On Muscle Oxygenationmentioning
confidence: 99%
“…The authors computed the ratio of walking events to upright events to provide an Event-Based Claudication Index and reported that this index was greater in PAD patients with intermittent claudication than in controls. Other studies reported associations in PAD patients between walking pattern and clinical, physiological, or biological features (Gardner et al, 2010b(Gardner et al, , 2010c(Gardner et al, , 2011b(Gardner et al, , 2012b(Gardner et al, , 2014cRitti-Dias et al, 2011;Gardner et al, 2015).…”
Section: Characterization Of Ambulatory Walking Patternmentioning
confidence: 98%
“…Besides the assessment of additional dimensions of PA by measuring the intensity or the duration of ambulation, the study of ambulatory walking pattern is of particular interest in PAD patients since it can be modified because of claudication (McDermott et al, 2001b;Gardner et al, 2010c). The StepWatch 3 ™ (Gardner et al, 2007b(Gardner et al, , 2008(Gardner et al, , 2010b(Gardner et al, , 2010c(Gardner et al, , 2011b(Gardner et al, , 2012b(Gardner et al, , 2014cRitti-Dias et al, 2011;Gardner et al, 2015) and the activPAL ™ (Clarke et al, 2013;Stansfield et al, 2015) are the two ambulatory devices currently used in PAD patients for such purpose (Supporting Information Appendix S2 and S3). Although these devices have been extensively used and validated across different populations, validity studies Physical activity and walking capacity in PAD conducted specifically in PAD patients are lacking.…”
Section: Characterization Of Ambulatory Walking Patternmentioning
confidence: 99%
“…Walking economy (WE), defined as the steady-state aerobic demand for a given submaximal speed of walking, 1 is abnormal in some vascular, neurological and orthopedic disorders. 2 Increased energy expenditure during walking (i.e, poor economy) has been linked to such conditions as peripheral arterial disease, 3 stroke, 4 spinal cord injury, 5 amputation, 6 and cerebral palsy. 7 In men with Parkinson's disease (PD), there was a trend for energy to be increased relative to healthy age and sex-matched controls.…”
Section: ■ Introductionmentioning
confidence: 99%